Habitus, Agency and Political Participation of Female Students: A Study at an Islamic University in Indonesia - Toyibah, Dzuriyatun (UI Scholars Hub, 2017)
This article aims to explain how and to what extent habitus and agency affect female students’ political participation. Habitus, as one of the concepts of Bourdieu, emphasizes the existence of disposition, in which actions are done without prior consideration and deliberation, and encourages people to repeteadly do similar acts simply because they are common practices in society. In contrast, agency emphasizes the ability of reflexivity and conscious thought. Applying in-depth interviews with 10 female activist and non-activist students at an Islamic university in Indonesia, the study found that the habitus in their families and neighborhoods prevented female students from obtaining equal positions to male students. Eventhough, as members of the student community, they conducted the reflexivity process, and thus had agency to act freely. This reflexivity, however, has not managed to achieve a complete patriarchal cultural change.